2007
DOI: 10.1590/s1413-86702007000300008
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of the factors associated with the risk of pneumonia in intensive care units

Abstract: Pneumonia is the most frequent hospital infection in patients admitted to intensive care units (ICU) and is also responsible for the highest lethality rates, as well as an increase in both the duration and costs of hospitalization. The objective of this study was to identify predisposing factors for pneumonia. A prospective cohort study was carried out between June 1996 and June 1997, and included 540 patients admitted consecutively for periods greater than 24 hours to the adult ICU of the Londrina State Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
2
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
(13 reference statements)
2
5
2
8
Order By: Relevance
“…Although many studies have shown tracheotomy to be a major risk factor for VAP development [13][14][15][16][17][18][19] , our study results do not support that claim. Our data suggest that lower VAP incidences are to be expected in tracheotomized patients.…”
Section: Resultscontrasting
confidence: 98%
See 1 more Smart Citation
“…Although many studies have shown tracheotomy to be a major risk factor for VAP development [13][14][15][16][17][18][19] , our study results do not support that claim. Our data suggest that lower VAP incidences are to be expected in tracheotomized patients.…”
Section: Resultscontrasting
confidence: 98%
“…The impact of tracheotomy on the development of VAP is not clearly defined. Some studies found decreases in VAP rates in patients having tracheotomy [6][7][8][9][10][11][12] , others have reported tracheotomy to be a risk factor favoring VAP onset [13][14][15][16][17][18][19][20] , while some could not demonstrate any VAP-related impact whatsoever [21][22][23][24] . Because of the conflicting literature data, there is currently no consensus on tracheotomy as either a VAP-protective or VAP-causative factor 5 .…”
Section: Introductionmentioning
confidence: 99%
“…As consequências do uso de antimicrobianos em pequenos animais não diferem da medicina humana e a quantidade e padrão de uso determinam as taxas de desenvolvimento de resistência (RANTALA et al, 2004;CARRILHO et al, 2007) Observa-se em geral aumento da resistência a antimicrobianos em pequenos animais, de acordo com o maior ou menor uso do produto: em Staphylococcus coagulase-positivo isolados de infecções da pele, orelhas e mucosa de cães no período de 1980-1996 no Reino Unido, houve aumento da resistência à penicilina de 69% para 89%, enquanto a resistência à oxitetraciclina permaneceu constante em 40% (GUARDABASSI; . Na Finlândia, comparou-se 22 cães com desordens dermatológicas tratados com diversos antimicrobianos em relação a 56 cães não tratados, constatando-se que havia mais Staphylococcus spp multirresistentes no grupo tratado e que os isolados de Staphylococcus spp dos cães tratados eram mais resistentes à sulfametoxazol-trimetoprima, penicilina, e lincosamidas, porém a resistência à oxacilina foi rara (RANTALA et al, 2004).…”
Section: O Aumento Da Resistência Antimicrobiana Em Animaisunclassified
“…O S. aureus resistente à meticilina (MRSA) é um problema de relevância em medicina humana, se constituindo em uma das principais causas de infecção em pacientes hospitalizados CARRILHO et al, 2007); este microorganismo também está despontando como causa de infecção comunitária em pessoas sem fatores de risco para a ocorrência de infecção hospitalar (CAPOBIANGO et al, 2007;SASAKI et al, 2007;NORMANNO et al, 2007). Em seres humanos é causa comum de infecções cutâneas superficiais e invasivas, como septicemias/ bacteremias, pneumonia, osteomielite, infecção do sítio cirúrgico e endocardite (CAPOBIANGO et al, 2007;UMBER;BENDER, 2009), restando poucas opções terapêuticas contra este microorganismo (PELLISSON et al, 2010).…”
Section: Staphylococcus Resistente à Meticilinaunclassified
See 1 more Smart Citation